Resilience as mediator in the relationship between family functioning and depression among adolescents from single parent families - Ng, Ying Yee; Wan Shahrazad Wan Sulaiman, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Family dysfunction makes many adolescents experience problems in adjusting themselves in single-parent families. Resilient adolescents cope by interpreting life in single-parent family as a meaningful and empowering transition while non-resilient adolescents often experience anxiety and depression. This study aims to examine the mediator effect of resilience in the relationship between family functioning and depression among adolescents from single parent families. The participants were 232 adolescents who came from single parent families, with ages 13 to 18 years old. Data were collected from 8 secondary schools in Klang Valley using a set of questionnaire consisting the Family Adaptability and Cohesion Evaluation Scales III, The Resilience Scale and Beck Depression Inventory-II. Pearson correlation analysis showed that all the variables in this study were significantly correlated with each other. Results showed that resilience significantly mediated the relationship between family adaptability and depression. However, resilience partially mediated the relationship between family cohesion and depression. The strong emotional bonding among family members can serve as a significant social support for family members. When adolescents have adequate social support from their family, it will foster the process of resilience reintegration. Hence, family cohesion has a stronger relationship with resilience compared to family adaptability that emphasised on family’s leadership, rules and roles. This implies that adolescents from single parent family should be assisted in strengthening and building their resilience despite staying in the dysfunctional family to reduce their depression tendencies.